2011
DOI: 10.1007/s00436-011-2539-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the acaricide effect of thymol on larvae of the cattle tick Rhipicephalus microplus (Acari: Ixodidae) by solubilization in ethanol

Abstract: The aim of the present work was to propose a new method of solubilizing thymol for use as an acaricide and to evaluate the resulting product's efficacy on Rhipicephalus microplus larvae. Two experiments were performed, both employing the larval packet test to evaluate the potential of the solutions formulated. In the first experiment, R. microplus larvae were exposed to three new formulations: formulation 1-distilled water (70%) + ethanol (30%) + thymol (10.0 mg/ml); formulation 2-distilled water (50%) + ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 12 publications
(10 reference statements)
1
13
1
Order By: Relevance
“…However, this article reports the first experiment of the application of thymol in semi-natural conditions. The mortality observed here was above 95 % starting at a thymol concentration of 10 mg/mL, while in the in vitro study by Scoralik et al (2012), the same mortality percentage was observed starting at a concentration of 2.5 mg/mL. These differences can be related to the method used and the greater dissipation of thymol in open environments.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…However, this article reports the first experiment of the application of thymol in semi-natural conditions. The mortality observed here was above 95 % starting at a thymol concentration of 10 mg/mL, while in the in vitro study by Scoralik et al (2012), the same mortality percentage was observed starting at a concentration of 2.5 mg/mL. These differences can be related to the method used and the greater dissipation of thymol in open environments.…”
Section: Discussionmentioning
confidence: 66%
“…The acaricidal activity of thymol, a monoterpene found in essential oil of plants of the families Lamiaceae and Verbenaceae (Pengelly 2004), has already been demonstrated in vitro studies on larvae (Novelino et al 2007;Scoralik et al 2012) and engorged ). However, this article reports the first experiment of the application of thymol in semi-natural conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations